Problems of performance audit methodology in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2018)
Performance audit is a complex type of state audit, while being an important function in improvingpublic administration. The complexity of performance audit is related to the scope of issues and theamount of information that are subject to study and analysis during performance audit. The lack or inadequacyof regulations on the control of accounting and reporting systems is one of the main challengesin conducting performance audits. The quality of performance audit depends on the quality of the methodologicalframework for performance audit based on clear principles and on best practices, taking intoaccount changes in the global community. The purpose of this article is to analyze the main principlesand their interpretations in the system of state audit and recommend the basics of application based onthe objectives of performance audit. The study was conducted using the method of comparing the normsof legislation and provisions of international standards. The results of the research revealed problems ofinconsistency and incompleteness of the fundamental principles of performance audit. Authors proposeprinciples and their interpretation, taking into account the norms of legislation, the provisions of internationalstandards and the results of recent studies by authors of other countries.